2017
DOI: 10.1038/srep40316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of wood-boring beetles (Cerambycidae and Buprestidae) intercepted in trade-associated solid wood packaging material using DNA barcoding and morphology

Abstract: Global trade facilitates the inadvertent movement of insect pests and subsequent establishment of populations outside their native ranges. Despite phytosanitary measures, nonnative insects arrive at United States (U.S.) ports of entry as larvae in solid wood packaging material (SWPM). Identification of wood-boring larval insects is important for pest risk analysis and management, but is difficult beyond family level due to highly conserved morphology. Therefore, we integrated DNA barcoding and rearing of larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…In one case, Xylosandrus crassiusculus, our data clearly shows that it is a highly variable (i.e., COI haplotypes) monophyletic species and not three potential cryptic species (Ashfaq and Hebert, 2016). Taking these steps to improve species identification and verification of species in current global databases will improve accuracy of the DNA barcodes (Wu et al, 2017) and applications to biodiversity assessment or the testing of ecological hypotheses (e.g., Caesar et al, 2006;Cognato and Caesar, 2006;Miller et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In one case, Xylosandrus crassiusculus, our data clearly shows that it is a highly variable (i.e., COI haplotypes) monophyletic species and not three potential cryptic species (Ashfaq and Hebert, 2016). Taking these steps to improve species identification and verification of species in current global databases will improve accuracy of the DNA barcodes (Wu et al, 2017) and applications to biodiversity assessment or the testing of ecological hypotheses (e.g., Caesar et al, 2006;Cognato and Caesar, 2006;Miller et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Identification of immature stages to species or genus presents the greatest challenge even for experts. This taxonomic impediment could be remedied in part by the creation of a DNA database based on expertly identified specimens, as with other wood-boring beetles (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Wu et al . ). The molecular analysis in this study showed Australian specimens that represent a distinct group with marked COI divergences from S .…”
Section: Resultsmentioning
confidence: 97%
“…The mtDNA is inherited most often only from the mother and does not undergo recombination 41 , enabling to assess the number of genetically unique founder females [42][43][44][45] . Studies of invasive species used similar methodologies, for example of T. peregrinus 16 , wood-boring beetles 46 , Melanagromyza sojae (Zehntner, 1900) (Diptera: Agromyzidae) 47 and Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) 48 .…”
Section: Possible Invasion Routes Of T Peregrinus In South America mentioning
confidence: 99%